Beiträge ungarischer Strafrechtswissenschaftler im NS-Deutschland und in Ungarn (1933–1944) - Lehotay, Veronika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
In this paper I examine the changes in Hungarian criminal law in the aspect of how German law affected the Hungarian. I also present how the Hungarian criminal law literature appeared in Germany during the Hitler era. I deal with two examples in the study: the issue of criminal protection of the state, and racial protection.